Correlation Between Serum Prostatic Specific Antigen and Prostatic Volume in Prostatic Hyperplasia - Agrahari, Mahendra Kumar; Shrestha, Joon Kumar; Singh, Ranjita; Sapkota, Kalyan; Shah, Kamlesh Kumar (Journal of College of Medical Sciences-Nepal, 2024)
Background Prostate specific antigen (PSA) is a serine protease produced by the prostate epithelium and per urethral glands in male. Serum PSA elevation occurs as a result of disruption of normal prostatic architecture that allows PSA to diffuse into prostatic tissue and gain access to the circulation. Prostatic hyperplasia is a progressive condition characterized by prostate enlargement accompanied by lower urinary tract symptoms (LUTS). Methods The objective is to investigate the correlation between serum PSA levels and trans abdominal USG prostate volume in clinically diagnosed cases with prostatic hyperplasia. This is a hospital based study conducted in the Department of Radiology and Medicine at Bharatpur Hospital. All cases diagnosed clinically underwent USG by radiologist and serum PSA estimation was done in the lab by Elisa method. 150 cases were studied. Results Age of 51-60 years with a percentage of 29.30%, consisted of 67 patients with a volume of 20.00-39.99 cc (44.7%), 87 patients with PSA levels of <2.6 ng/mL (58.0%), prostate volume is 20.00-> 80 cc at the age of 51-60 years, PSA levels <2.6->20 ng / mL at the age of 51-60 years and value of p = 0,000 (p<0.05) and the value of r = 107.57, implying that prostate volume and PSA levels has a significant and strong correlation. Conclusions There is a significant association between prostate volume and PSA levels in BPH patients in our study, with p = 0,000 and r =107.59 showing a strong positive correlation.